Analysis of Joint Venture in China’s Automotive Industry - Fung, Kin Wa (2012)
This research study aims to better understand whether it is still the best option for the Chinese Government to force foreign companies into the joint venture business strategy to enter into the Chinese Domestic Market. This is an investigation into the feasibility and impact of the joint venture strategy analysing the internal and external factors that influence the performance of joint venture firms. Internal factors include the R&D, management and marketing/sales distribution and external factors such as government policy. To summarise the findings the joint venture strategy has proven to be a successful mode to enter the Chinese Domestic Market this is because it is financially beneficial to both the foreign company and the local Chinese partner, although it can be said that there is controversy over the forced requirement of a local partner, this remains an essential and mandatory requirement by the Chinese industry policy. The findings highlight key problems such as foreign partners not willing to transfer their key technologies to their local partners and as a result domestic vehicle companies are focusing more on achieving sales, regardless of brand origination.